The Effect of COVID on Oral Reading Fluency During the 2020-2021 Academic Year - Benjamin W. Domingue; Madison Dell; David Lang; Rebecca Silverman; Jason Yeatman; Heather Hough (SAGE Publishing, 2022)
Education has faced unprecedented disruption during the COVID pandemic. Understanding how students have adapted as we have entered a different phase of the pandemic and some communities have returned to more typical schooling will inform a suite of policy interventions and subsequent research. We use data from an oral reading fluency (ORF) assessment-a rapid assessment taking only a few minutes that measures a fundamental reading skill-to examine COVID's effects on children's reading ability during the pandemic. We find that students in the first 200 days of the 2020-2021 school year tended to experience slower growth in ORF relative to prepandemic years. We also observe slower growth in districts with a high percentage of English language learners and/or students eligible for free and reduced-price lunch. These findings offer valuable insight into the effects of COVID on one of the most fundamental skills taught to children.